Infrequent attention to dietary and physical activity behaviours in conversations in Swedish child health services. (12th February 2013) - Bohman, B; Eriksson, M; Lind, M; Ghaderi, A; Forsberg, L; Rasmussen, F
Abstract Aim To investigate conversations between nurses and parents in Swedish child health services and to assess to what extent attention is directed towards dietary and physical activity behaviours in children. Methods Twenty‐three nurses audio‐recorded one session each. Recordings were assessed and topics were classified according to predetermined categories. Results The three most frequent topics of conversation concerned physical examinations of the child (30% of session time), talking to the child to establish or maintain contact and interest (15%), and development of language skills (12%). Dietary habits came on fourth place (10%), and physical activity ranked 14 (4%). Conclusion Attention to dietary and physical activity behaviours in children is infrequent in Swedish child health services. Concern is raised about the efficacy of prevention efforts against childhood obesity.